'Enemies of the people': Donald Trump and the security imaginary of America First. (August 2022) - Löfflmann, Georg
The discursive domain of (in)security is integral to nationalist populism, as documented in the political rhetoric of Donald Trump. This article combines insights from political psychology on blame attribution with scholarship in International Relations on security narratives to show how the reframing of national identity through a populist security imaginary elevated internal 'enemies of the people' to an ontological status of equal, or even superior standing to that of external threats to national security. Portraying internal and external Others as equally existential threats endangering the 'real' United States informed both foreign policy choices and mobilised voters through an affective persuasion of audiences, actively dividing society for political gain. Populist appeals to resentment, fear, and anxiety constituted a shared affective space between Trump and his followers that provided a source of mutual ontological reassurance and the legitimation of America First measures from immigration restrictions to trade protectionism and a Jacksonian foreign policy.